CHAPTER 10 NO SMOKING POLICIES AT THE WORKSITE A LOOK AT WHAT COMPANIES ARE DOING TODAY - BEHRENS,R (Tufts Archival Research Center, 2007)
Chapter from a book on the trend in workplace smoking bans over the past few decades. Discusses the change in the attitude toward smoking and how that has affected the workplace smoking policies Lists several questions that should be asked before any type of regulation is implemented and goes over the pros and cons of a workplace ban.